Inflation and Conflict in Iraq : The Economics of Shortages Revisited - Kock, Udo (IMF Working Papers; Working Paper ;, 2010)
Containing inflation has turned out to be one of the most challenging aspects of economic management in Iraq. This paper posits that conventional as well as unconventional factors explain inflation dynamics in the recent past. We build a theoretical model based on the insights into the workings of socialist economies under supply shortages provided by Shleifer and Vishny (1992) to help explain price dynamics. In the model, strategic behavior of the fuel distribution monopolist results in fuel shortages, with implications for fuel and non-fuel inflation. A number of step-wise adjustments of administered prices for fuel products since December 2005 offer an interesting experiment to help study this behavior. Our findings show that inflation may have been influenced by shortages in fuel and non-fuel commodity supplies, which themselves are driven by violence and rent-seeking.